Sensors and Instrumentation, Aircraft/Aerospace and Energy Harvesting , Volume 8 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Wee Sit, Evro.; Walber, Chad.; Walter, Patrick; Wicks, Alfred; Seidlitz, Steve; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Sensors and Instrumentation, Volume 8.  Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the eighth volume of nine from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Sensors and Instrumentation, including papers on: Sensor Applications Accelerometer Design Accelerometer Calibration Sensor Technology Energy Harvesting Technology Aircraft/Aerospace Technology.
Chapter 1. Broadband Energy Harvesting Performance of a Piezoelectrically Generated Bistable Laminate -- Chapter 2. Performance Assessment of Several Low-Cost Consumer-Grade Analog-to-Digital Conversion Devices -- Chapter 3. High-g Shock Acceleration Measurement using Martlet Wireless Sensing System -- Chapter 4. Effect of Piezoelectric Material in Mitigation of Aerodynamic Forces -- Chapter 5. A Theoretical Description of a Multi-source Energy Harvester -- Chapter 6. Lumped Mass Model of a 1D Metastructure with Vibration Absorbers with Varying Mass -- Chapter 7. Dynamic Behavior and Performance Analysis of Piezoelastic Energy Harvesters Under Model and Parameter Uncertainties -- Chapter 8. Experimental Test of Spacecraft Parachute Deployment using Real-Time Hybrid Substructuring -- Chapter 9. Experimental and Analytical Approaches in a Virtual Shaker Testing Simulation Environment for Numerical Prediction of a Spacecraft Vibration Test -- Chapter 10. Direct Reference-free Dynamic Deflection Measurement of Railroad Bridge under Service Load -- Chapter 11. A Low-Cost Modular Impact-Based Experimental Setup for Evaluation of EMI Based Structural Health Monitoring at High Rates -- Chapter 12. Real-time Low-cost Wireless Reference-free Displacement Sensing of Railroad Bridges -- Chapter 13. Multi-tonal Based Impedance Measurements for Microsecond State Detection -- Chapter 14. Design and Installation Considerations of Dynamic Strain Gages for Thermo-Acoustic Aerospace Structures Test -- Chapter 15. TESS Vibration Testing: A Boundary Condition Case Study -- Chapter 16. Performing a Large-Scale Modal Test on the B2 Stand Crane at NASA's Stennis Space Center -- Chapter 17. Study on the Soft Suspension Behavior for Aircraft Ground Vibration Test Set-up -- Chapter 18. A Review of the Vibration Environment Onboard Small Unmanned Aircraft.
Keywords: Aerospace engineering; Astronautics; Multibody systems; Vibration; Mechanics, Applied; Energy harvesting; Electric power production; Aerospace Technology and Astronautics; Multibody Systems and Mechanical Vibrations; Energy Harvesting; Electrical Power Engineering; Mechanical Power Engineering